Measuring the Bandgap of Ambipolar 2D Semiconductors using Multilayer Graphene Contact. Issue 2 (22nd December 2022) - Park, Sam; Hong, Sungjae; Lim, June Yeong; Yu, Sanghyuck; Kim, Jungcheol; Cheong, Hyeonsik; Im, Seongil
Abstract : The bandgaps of monolayers and few layers in 2D semiconductors are usually measured by optical probing such as photoluminescence (PL). However, if their exfoliated thickness is as large as a few nanometers (multilayer over ≈5 L), PL measurements become less effective and inaccurate because the optical transition of a 2D semiconductor often changes from direct to indirect mode. Herein, a simple method to approximately estimate the bandgap of multilayer 2D van der Waals (vdW) semiconductors is introduced; that is utilizing a field‐effect transistor (FET) as a platform. Multilayer graphene (multi‐LG) contact for multilayer van der Waals channels in the FET is used, because multi‐LG contact would secure ambipolar behavior and somewhat enable Schottky barrier modulation in contact with vdW channels. As a result, the bandgaps of multilayer transition‐metal dichalcogenides (TMDs) and black phosphorus in unknown thicknesses are approximated through measuring the temperature‐dependent transfer curve characteristics. The bandgaps are confirmed with photoelectric responsivity measurements, which evidences the validity of the multi‐LG‐induced approximation. Abstract : A novel bandgap estimation technique utilizing a multilayer graphene (multi‐LG) source/drain contact field‐effect transistor (FET) as a platform is introduced. The gate‐voltage tunability of Schottky barrier at the 2D material/multi‐LG junction makes it possible to extract the half‐bandgap value from the temperature‐dependent transfer characteristics of the FET. The bandgaps of multilayer transition‐metal dichalcogenides (TMDs) and black phosphorus are approximated with the technique.